-8y-2=-9-3y

Simple and best practice solution for -8y-2=-9-3y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8y-2=-9-3y equation:


Simplifying
-8y + -2 = -9 + -3y

Reorder the terms:
-2 + -8y = -9 + -3y

Solving
-2 + -8y = -9 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
-2 + -8y + 3y = -9 + -3y + 3y

Combine like terms: -8y + 3y = -5y
-2 + -5y = -9 + -3y + 3y

Combine like terms: -3y + 3y = 0
-2 + -5y = -9 + 0
-2 + -5y = -9

Add '2' to each side of the equation.
-2 + 2 + -5y = -9 + 2

Combine like terms: -2 + 2 = 0
0 + -5y = -9 + 2
-5y = -9 + 2

Combine like terms: -9 + 2 = -7
-5y = -7

Divide each side by '-5'.
y = 1.4

Simplifying
y = 1.4

See similar equations:

| 3/4(z)=-18 | | x^2+2x+42=0 | | -8=k-11 | | y=3.8x | | 2n-6=6-2n | | p=r | | 55=6*8+7 | | 3y=-2x-1 | | -14x^2-29x-12=0 | | 47.582-0.01(0.2+3x)=7.9x | | M=150+38x | | m-7=-10 | | 0=-8p-6p | | 10=v/2 | | -x-8=2y | | 39=-4x-1 | | -5(x-1)+6= | | 75x^2+65x+10=0 | | 19=m+7-3m | | -12+5k=15-14k | | 30d+12=18d | | 19=9x-8 | | 6x+11=-133 | | -12+x=-2 | | -5x-1=2-(x+4) | | py+yn=x | | 3+8x-2=17 | | 9r+10=55 | | 0.3-2.91=5-0.2(3-0.01x) | | 7(2+x)+6x= | | -3x-3=-3x+-3 | | y=-200x+1880 |

Equations solver categories